Lessons in Secular Criticism - Gourgouris, Stathis, 1958- (Book collections on Project MUSE., 2013)
Secular criticism is a term invented by Edward Said to denote not a theory but a practice that counters the tendency of much modern thinking to reach for a transcendentalist comfort zone, the very space philosophy wrested away from religion in the name of modernity. Using this notion as a compass, this book reconfigures recent secularism debates on an entirely different basis, by showing (1) how the secular imagination is closely linked to society's radical poiesis, its capacity to imagine and create unprecedented forms of worldly existence; and (2) how the space of the secular animates the de.